Analysis of microbial communities in Rusitec and single-flow continuous culture fermenters by PCR-SSCP: effects of basal diet - Ranilla M.J.; Martín García A.I.; Molina Alcaide E.; Carro M.D. (Nutritional and foraging ecology of sheep and goats, 2009)
The aim of this work was to analyse microbial communities in two artificial rumen systems, Rusitec and single-flow continuous culture fermenters (SFCCF), fed two diets containing alfalfa hay and concentrate in the proportions of 80:20 and 20:80. Eight fermenters of each type were run for 14 days. On days 13 and 14, total effluent was collected and homogenized in a blender at low speed for 1 min and lyophilized. In order to study microbial diversity, DNA was isolated from samples (120 mg) of lyophilized effluent and the V3-4 region of the 16S rDNA gene was amplified by PCR and analysed by using single-strand-conformation polymorphisms (SSCP). Distinct clusters were observed for Rusitec and SFCCF samples. Microbial diversity, assessed using Shannon's index (H') was higher (P < 0.01) in SFCCF than in Rusitec. Within systems, samples were grouped together according to diet, but H' was not affected (P > 0.05) by diet or system. Similarity between fermenters in PCR-SSCP banding patterns was higher in the Rusitec than in SFCCF for both diets. Under the conditions of the present experiment, microbial populations were affected by diet in both systems, and microbial diversity was different in both types of fermenters.
12. Seminar on: Nutritional and Foraging Ecology of Sheep and Goats, 2007/10/11-13, Thessaloniki (Greece)